Manipulative techniques in Ukrainian religious media discourse - Levko, Oleksandr (Current issues of Ukrainian linguistics: theory and practice, 2018)
The article analyses communicative strategies in the Ukrainian interconfessional media discourse with the particular focus on investigation of the manipulative techniques, based on publications of the religious internet portals "Religijno-informatsijna sluzhba Ukrajiny", "Katolytskyj ogljadach" and "Religija v Ukrajini". It is established that the texts dealing with interconfessional questions resort to manipulative techniques with the purpose of making the audience take a particular viewpoint to important issues in the field of interconfessional relations, as well as with the purpose of presenting the self in favorable light and discrediting ideological opponents. It is also revealed that the most common manipulative techniques, used in the Ukrainian interconfessional media discourse, are name-calling, misuse of concepts, appealing to ideological mythologems, black-white depiction and the use of emotional appeals. It is demonstrated that the ideological mythologems "Russian world", ''Post-Christian Europe", ''Saint Rus", "Godless West", "holy war", "defense of Christians" are used with negative connotations in the Ukrainian interconfessional media texts as means of communicative strategy of opponents’ discrediting.
Keywords: religious media discourse, manipulative strategies, name calling, ideological mythologems, interconfessional dialogue.